1990
DOI: 10.1056/nejm199010043231402
|View full text |Cite
|
Sign up to set email alerts
|

Location on Chromosome 15 of the Gene Defect Causing Marfan Syndrome

Abstract: The chromosomal localization of the mutation in Marfan syndrome is a first step toward the isolation and characterization of the defective gene and serves as a diagnostic test in families in which cosegregation of these markers with the disease has been confirmed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
108
0
12

Year Published

1992
1992
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 347 publications
(121 citation statements)
references
References 24 publications
1
108
0
12
Order By: Relevance
“…8 The following year, the gene encoding fibrillin-1 (FBN1) was cloned and the first mutations in the gene were identified in Marfan syndrome patients. 9 -11 Interestingly, the year before the FBN1 gene was cloned, Kainulainen et al, 12 demonstrated through linkage analysis that the gene involved in classic complete forms of the Marfan syndrome was located on human chromosome 15 precisely where the FBN1 gene was later located. Therefore the identification of the gene defect in Marfan syndrome is a rare example in which both positional and functional cloning strategies converged rapidly to identify a disease gene.…”
Section: The Marfan Syndrome and Fbn1mentioning
confidence: 99%
“…8 The following year, the gene encoding fibrillin-1 (FBN1) was cloned and the first mutations in the gene were identified in Marfan syndrome patients. 9 -11 Interestingly, the year before the FBN1 gene was cloned, Kainulainen et al, 12 demonstrated through linkage analysis that the gene involved in classic complete forms of the Marfan syndrome was located on human chromosome 15 precisely where the FBN1 gene was later located. Therefore the identification of the gene defect in Marfan syndrome is a rare example in which both positional and functional cloning strategies converged rapidly to identify a disease gene.…”
Section: The Marfan Syndrome and Fbn1mentioning
confidence: 99%
“…It has an autosomal dominant mode of transmission mainly affecting the connective tissue protein fibrillin [2].The defect itself has been isolated to the FBN1 gene on chromosome 15, which codes for the connective tissue protein fibrillin [3].…”
Section: Introductionmentioning
confidence: 99%
“…La subluxation du cristallin et les articulations hyperextensibles ont été décrites en 1873, l'hérédité autosomale dominante en 1931, la dilatation de la racine aortique et le risque de rupture en 1943, et la dé-couverte de la fibrilline-1 anormale comme base de cette maladie en 1990 [3]. La localisation du gène du syndrome de Marfan sur le chromosome 15 s'est faite la même année par analyses de couplage [4], et la première preuve de mutations pathogènes du gène de la fibrilline-1 a été donnée en 1991 [5]. Nous connaissons aujourd'hui environ 500 mutations diffé-rentes [6].…”
Section: Introductionunclassified